Pengaruh Pengetahuan Perpajakan, Modernisasi Sistem Administrasi Perpajakan, Kualitas Pelayanan Pajak, Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak - oktaviana agustania waru (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of knowledge taxation, modernization of tax administration system, the quality of tax service and taxpayer awareness of taxpayer compliance on KPP Pratama Ruteng. This type of research is quantitative research. The population in this study are taxpayers registered in KPP Pratama Ruteng. Data collection was done directly by using questionnaire. Data analysis in this research using multiple regression with SPSS program version 16.0. The results showed that the value of F arithmetic 28.149 greater than F table 2.74. These results indicate that the knowledge of taxation, modernization of tax administration system, the quality of tax services, and awareness of taxpayers can affect simultaneously to taxpayer compliance. Partially knowledge of taxation (X1), modernization of tax administration system (X2), quality of tax service (X3), and awareness of taxpayer (X4) have a positive effect significantly to taxpayer compliance. This result is evidenced by t count> t table 1.66864 and significance <0.05, ie (a) 2.031 and 0.046 (X1Y1), (b) 3.024 and 0.003 (X4Y1). Modernization of tax administration system (X2) and quality of tax service (X3) have no significant effect to taxpayer compliance. This is evidenced by the niali t arithmetic <t table 1.66864 and the significance> 0.05, ie (a) 0.167 and 0.868 (X2Y1), (c) 0.366 and 0.715 (X3Y3). Keywords: Knowledge of taxation, modernization of tax administration system, quality of tax service, awareness of taxpayer, taxpayer compliance